A Synthesizable Ethernet Switch with Enhanced Real-Time Features - Rui Santos (2009)
The use of switched Ethernet for safe real-time communication still suffers from undesired phenomena, such as blocking caused by long non-preemptive frames, lack of protection against errors in the time domain, couplings across virtual LANs and priority levels via internal switch shared resources. Recently, a few solutions were proposed to cope with such phenomena. One such solution is based on an enhanced switch following the Flexible Time-Triggered paradigm, which enforces strict service differentiation with any kind of traffic scheduling, blocking-free forwarding and timing errors confinement. In this paper we propose a new architecture following an hardware-software co-design approach that simplifies the development of the enhanced switch features by detaching the traffic scheduling from the traffic switching. The paper shows experimental results with an actual switch prototype that confirm the desired switch properties.